Treatment of osteoporosis with eldecalcitol, a new vitamin D analog: a comprehensive review and meta-analysis of randomized clinical trials - Xu Z; Fan C; Zhao X; Tao H (Dove Medical Press, 2016)
Zhixing Xu,1 Changchun Fan,2 Xuechun Zhao,3 Hairong Tao1 1Department of Orthopedic Surgery, The Third People’s Hospital Affiliated to Shanghai Jiaotong University School of Medicine, Shanghai, People’s Republic of China; 2Department of Orthopedic Surgery, Jinan Military General Hospital, 3Department of Orthopedic Surgery, The Third Hospital of Jinan City, Jinan, People’s Republic of China Objective: Eldecalcitol (ELD) is an active form of vitamin D analog that has been approved for the treatment of osteoporosis in Japan. Over recent years, a number of multicenter, randomized controlled clinical trials have been conducted. Our goal is to comprehensively summarize the results from these studies.Methods: We searched the databases MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials up to February 28, 2015. Each database was searched using search terms “Eldecalcitol” and “ED-71” and the results were combined. The retrieved data from three independent clinical trials included a total of 1,332 patients with osteoporosis. After the data were pooled from three trials, RevMan software was used to conduct meta-analyses to determine the effects of ELD on bone mineral density (BMD) and bone turnover marker (BTM) type I collagen amino-terminal telopeptide (NTX). Effects of ELD on some of the bone formation and bone resorption parameters, incidence of vertebral fractures at the lower spine, and health-related quality of life (HRQOL) in patients with osteoporosis were also summarized. Results: With a test for overall effect Z=6.35, ELD could increase lumbar BMD (P<0.00001). In comparison with alphacalcidol, ELD suppressed the NTX level to a greater degree (test for overall effect Z=3.82, P<0.0001). ELD was also found to suppress bone alkaline phosphatase (BALP) by 19% (P<0.01) and osteocalcin by 19% (P<0.01) at the dose of 0.75 µg/day. Compared to alfacalcidol, ELD showed higher potency in suppressing serum BALP (26±9 vs 32±11 U/L, P<0.05) and amino-terminal propeptide of procollagen I (PINP) (42±15 vs 59±23 ng/mL, P<0.05). In addition, ELD was found to be more effective in reducing the incidence of vertebral fractures at the lower spine (P=0.029). Conclusion: Our meta-analysis showed that ELD was more potent than alphacalcidol in reducing BTM (NTX). Clinical data together suggest that ELD is efficient in treating osteoporosis by increasing lumbar BMD; suppressing BTMs, including NTX, BALP, osteocalcin, and PINP; resulting in the reduction in the incidence of vertebral fractures at the lower spine; and increasing the HRQOL in patients with osteoporosis. Keywords: BMD, NTX, BALP, PINP